Pseudomyxoma Peritonei Originating from an Intestinal Duplication. (19th August 2013) - Lemahieu, Julie; D'Hoore, André; Deloose, Stijn; Sciot, Raf; Moerman, Philippe
Abstract : Alimentary tract duplications are rare congenital anomalies. They most often become symptomatic in childhood and rarely undergo malignant transformation. Pseudomyxoma peritonei (PMP) is an equally uncommon condition, most frequently originating from a primary appendiceal mucinous neoplasm. We report an extremely unusual case of PMP arising from an intestinal duplication. A 67-year-old woman presented with vague upper abdominal pain, and, unexpectedly, explorative laparoscopy revealed diffuse jelly-like peritoneal implants. The histopathological diagnosis of a low-grade PMP or "disseminated peritoneal adenomucinosis" was made. At that moment, no primary tumor was found. During later surgery, a cystic lesion located in the mesentery of the small bowel could be resected. Histologically, the cyst wall clearly showed the concentric layering of a normal bowel wall. The mucosa, however, displayed a diffuse low-grade villous adenoma. We concluded that this histological picture was most consistent with a small intestinal duplication, containing a low-grade villous adenoma. The adenoma caused a mucocele, which subsequently leaked or ruptured, giving rise to noninvasive mucinous peritoneal implants or low-grade PMP, also known as "disseminated peritoneal adenomucinosis" (DPAM).